2017
DOI: 10.12659/msm.898075
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Physiotherapy for Total Ankle Replacement in Patients with Inherited Bleeding Disorders: Outline of an Algorithm

Abstract: The treatment of end-stage hemophilic arthropathy of the ankle joint remains a controversial problem, and total ankle replacement (TAR) is considered to be a valuable management option. Physiotherapy continues to be an extremely important part of TAR and has a tremendous impact on the outcomes of this procedure. Given the lack of data on the latter, this study details a protocol of perioperative physiotherapy in TAR in patients with inherited bleeding disorders (IBD).The protocol outlined in this paper was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Few studies have reported on the frequency of rehabilitation or PT, or provided discussion regarding rehabilitation approaches following TAA. 3,17,19,30 Accordingly, the frequency, patient perceived value, and potential influence PT has on patient-reported outcomes is unexplored. However, obtaining a profile of PT use and value is the first step to developing and modifying current rehabilitation approaches to leverage TAA operative success.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on the frequency of rehabilitation or PT, or provided discussion regarding rehabilitation approaches following TAA. 3,17,19,30 Accordingly, the frequency, patient perceived value, and potential influence PT has on patient-reported outcomes is unexplored. However, obtaining a profile of PT use and value is the first step to developing and modifying current rehabilitation approaches to leverage TAA operative success.…”
Section: Introductionmentioning
confidence: 99%